Aggressive Worriers: How Aggression Moderates the Association between Intolerance of Uncertainty and Suicidal Desire Constructs. Issue 3 (3rd July 2021) - Martin, Rachel L.; Smith, Nicole S.; McGrew, Shelby J.; Capron, Daniel W.
Abstract : Suicide is a public health concern and has been the tenth leading cause of death in the United States since 2008. The Interpersonal-Psychological Theory of Suicidal Behavior is an empirically supported model of suicide. The theory posits that thwarted belongingness and perceived burdensomeness examine the individual's perceived connectedness to others around them and together create suicidal desire. Anxiety is another widespread public health concern, associated with suicidal ideation and suicide attempts above and beyond the effects of socio-demographic factors and other mental disorders. A key factor in anxiety disorders is intolerance of uncertainty, or the individual's tendency to perceive ambiguous situations and events as being aversive to emotional and behavioral well-being. Additionally, different facets of aggression have been associated with both intolerance of uncertainty and suicidal desire. The current study sought to examine how facets of aggression moderated the associations between intolerance of uncertainty (both prospective and inhibitory) and thwarted belongingness/perceived burdensomeness. Participants were 440 adults recruited online. The hypotheses of aggression facets moderating the association between intolerance of uncertainty and perceived burdensomeness were largely supported with statistical significance for six out of eight models. Similarly, the hypotheses of aggression facets moderating thwarted belongingness were largely supported with significant moderations for seven out of eight models. The results were upheld when using Benjamini-Hochberg test of significance to account for Type I error. Overall, results indicate that aggressive facets can amplify the associations between intolerance of uncertainty and thwarted belongingness/perceived burdensomeness; however, results differed based on the intolerance of uncertainty dimensions.